LEGAL POLITICS IN DETERMINING THE PRESIDENTIAL THRESHOLD WITHIN INDONESIA’S CONSTITUTIONAL SYSTEM - Moza Dela Fudika; Ellydar Chaidir; Umi Muslikhah; Dandy Indra Octadinata (Jurnal Kajian Ilmu Hukum, 2025)
The elimination of the presidential threshold system on the one hand has had a positive impact on the development of Indonesian democracy. This system can restore the basic rights of citizens in the constitution (remedy of constitutional rights) that were once injured by the existence of the presidential threshold. There are many benefits that will be obtained by non-majority parties so that they can propose their respective presidential candidates, and also make the choice of president more diverse. With the PT, it will be easier for the president to carry out government duties, because there is no intervention from other dominant parties in parliament. However, the weaknesses of the elimination of the PT are also worth considering, such as the vulnerability of individual interests that can be obtained through presidential nominations. From a national security aspect, it will result in an expansion of conflict escalation and election crimes due to the large number of candidates. In terms of efficiency, the allocation of the election budget will increase (high cost election). At least the allocation of election funds can be channeled to areas that can improve the welfare of other people. However, this assumption needs to be further proven with in-depth research on the efficiency of campaign funds.